Rancang Peta Jalur Angkutan Umum Berbasis Web Menggunakan HTML, CSS, dan JavaScript di Visual Studio - Tarigan, Duncan Dancin; Tommy, Tommy; Budiman, Arief (Universitas Harapan Medan, 2023)
brought in significant revenue for traders and tourism operators in Berastagi. Unfortunately,many visitors often get lost on their way to their destinations, highlighting the need forinformation regarding public transportation in Berastagi. This research aims to design a websitethat provides information about public transportation, route options, and applicable fare rates.The goal is to ensure that visitors to Berastagi can explore the city's attractions with ease andconfidence. Qualitative research methods with a case study approach were employed for thisstudy. Interviews were conducted with station personnel from various public transportationproviders using purposive sampling techniques. The research resulted in a user-friendly websitethat assists users in finding transportation options that meet their needs. Station personnel citedthe lack of inquiries from visitors and the absence of clear information on public transportationroutes as reasons for visitors choosing the wrong mode of transportation. In conclusion, thisresearch has developed a comprehensive web application that offers information on variouspublic transportation choices based on users' destinations when visiting Berastagi. Based on the survey questionnaire conducted by the author with 15 users of the website that has been created,it is concluded that satisfaction in using the website according to its function reaches 90%, whichis stated as excellent.